Screening of universal DNA barcodes for identifying grass species of Gramineae - Wang, Jianli; Yan, Zhenfei; Zhong, Peng; Shen, Zhongbao; Yang, Guofeng; Ma, Lichao (Frontiers in Plant Science, 2022)
There is currently international interest in applying DNA barcoding as a tool for plant species discrimination and identification. In this study, we evaluated the utility of four candidate plant DNA barcoding regions [rbcL, matK, trnL-F, and internal transcribed spacer (ITS)] in seven genera of Gramineae including Agropyron, Bromus, Elymus, Elytrigia, Festuca, Leymus and Lolium. Fourteen accessions were analyzed, and matK and ITS showed the highest species, subspecies, and variety discriminatory power, each resolving 11 accessions. Species discrimination using rbcL and trnL-F was lower, resolving 7 and 8 accessions, respectively. Subspecies and variety discrimination using rbcL and trnL-F could not identify 4 accessions of Agropyron. A technical system can be established using the proposed DNA barcode to rapidly and reliably identify the seven genera of Gramineae. This study serves as a “useful reference” for identifying genetic diversity of grass germplasm resources. It is very important to analyze the genetic diversity of grass germplasm using DNA barcoding. It can reveal the relatives of different species within the family and between different families, determine the related groups of important herbage, turfgrass and crops, and provide important background information for discovering excellent genes and improving varieties.